Absent endometrium due to balanced translocation [t(4;20)] presenting as primary amenorrhea - Aruna Nigam; Ayesha Ahmad; Swaraj Batra (Wolters Kluwer Medknow Publications, 2014)
Primary amenorrhea is defined as the absence of menarche by 16-18 years of age in the presence of well-developed secondary sexual characters. An incidence of 1-3% has been reported in women of reproductive age group. The etiology varies with anatomical, genetic and hormonal factors implicated in the causation of primary amenorrhea. We present a case of absent endometrium due to balanced reciprocal translocation (RCPTR), 46 XX t (4;20)(q12;q13.1) as primary amenorrhea.